Feminism Reflected in The Main Character in The Movie Little Women 2019 by Louisa May Alcott - Rorintulus, Olga A.; Rahmat, Subhan; Nurmaisyah, Nurmaisyah; Fitra, Muh. Al Fachrizah (English Education Department, 2024)
Feminism is an enduring social issue, persisting from ancient times to the present. The struggles of early feminists resonate today, with patriarchy still evident in modern media, such as Greta Gerwig's adaptation of Little Women. This research examines how Little Women portrays the social issues of feminism, focusing on the experiences of the main character. Utilizing Sugihastuti's feminist approach, which defines feminism as a movement advocating for equality between men and women across political, economic, educational, and social spheres, the study explores the film's depiction of these themes. Additionally, Betty Friedan's feminist theory is employed to delve deeper into the feminist issues presented. The findings highlight several key feminist themes, including the societal expectation that women must marry to secure their future, the notion that women's roles are confined to homemaking, and the resistance to these norms by characters who choose their paths. The film illustrates the tension between traditional expectations and the characters' desires for independence, revealing the complexities of feminism and its relevance in contemporary society. Through this analysis, the research underscores how Little Women reflects ongoing feminist struggles and challenges the persistent patriarchal norms, offering a nuanced portrayal of women's autonomy and empowerment